The influence of ionic strength on the characteristics of heat-induced soy protein aggregate nanoparticles and the freeze–thaw stability of the resultant Pickering emulsions. Issue 8 (26th July 2017) - Zhu, Xue-Feng; Zheng, Jie; Liu, Fu; Qiu, Chao-Ying; Lin, Wei-Feng; Tang, Chuan-He
Abstract : Soy protein nanoparticles as Pickering stabilizers can be induced by heating in the presence of NaCl. The Pickering emulsions with NaCl exhibited much better freeze-thaw stability than those without NaCl. Abstract : The improvement of the freeze–thaw stability of emulsions by interfacial engineering has attracted increasing attention in recent years. The present work investigated the potential of using soy protein isolate (SPI) aggregate nanoparticles as the Pickering stabilizers to improve the freeze–thaw stability of the resultant emulsions. SPI nanoparticles with different particle sizes and surface properties were fabricated through heating the SPI solutions (at a constant protein concentration of 2%, w/v) at 95 °C for 15 min, by varying the ionic strength ( I ) in the range of 0–500 mM. The nanoparticles fabricated at I values of 100–500 mM exhibited larger particle sizes and higher surface hydrophobicity, but poorer emulsification efficiency than those at I = 0.05 mM. The presence of NaCl during the nanoparticle fabrication resulted in the formation of a kind of gel-like emulsion with a high extent of droplet flocculation. The emulsion stabilized by SPI nanoparticles at I = 0.05 mM was highly susceptible to coalescence, flocculation and creaming upon freeze–thaw treatment, while those in the presence of NaCl exhibited excellent freeze–thaw stability. The much better freeze–thaw stability of the emulsions in the presence of NaCl (relative to that at I = 0.05 mM) was largely attributed to the gel-like network formation, rather than the salt itself. The results indicated that a kind of Pickering emulsion with excellent freeze–thaw stability, stabilized by heat-induced SPI nanoparticles, could be fabricated by heating the SPI solutions at I values of 100–500 mM. The findings would be of great relevance for providing important information about the development of food grade Pickering emulsions stabilized by protein-based particles, with potential applications in frozen food, or functional food formulations.